Psychiatric disorders associated with intimate partner violence and sexual violence in Thai women: Aresult from the Thai National Mental Health Survey - Panyayong, Benjaporn (Gen Psychiatr, 2018)
BACKGROUND: Intimate partner violence (IPV) and sexual violence (SV) occur commonly and are a violation of basic human rights. There are limited studies to date that examine the impact of IPV, SV and mental health outcomes in Thailand. AIMS: The objective of the present study was to estimate the prevalence of intimate partner physical violence and IPV in Thai women and the association between these forms of violence and psychiatric disorders. METHODS: The present study used data from a national cross-sectional, population-based, household design survey. This study analysed data from 3009 female respondents above the age of 18 who were interviewed in person using the World Mental Health-Composite International Diagnostic Interview V.3.0 (WMH-CIDI 3.0). We estimated the lifetime and the 12-month period prevalence of IPV and SV, the lifetime and the past 12- month period correlation of IPV/SV with psychiatric disorders and the OR for psychiatric disorders associated with these types of violence. RESULTS: There was only 5.2 % of the weighted sample that reported experiencing some form of violence, including reported rates of intimate partner physical violence of 3.5% and IPV of 2.0%. Women who had experienced IPV have a lifetime prevalence for common psychiatric disorders of 28.9%, for suicidal behaviours of 12.2% and for substance use disorders of 8.8%. Women who had experienced SV have a lifetime diagnoses for common psychiatric disorders of 21.4%, for suicidal behaviours of 16.5% and for substance use disorders of 19.4%. There was a statistically significant association between IPV/SV and being diagnosed with a psychiatric disorder during the past year and also during one’s lifetime. CONCLUSION: The association between IPV/SV and psychiatric disorders is significant; therefore, performing a formal assessment for a history of violence in psychiatric patients is often beneficial in refining the diagnosis and treatment.